Pelatihan Pembuatan Keripik Jambu Kristal sebagai Inovasi Produk Oleh-Oleh Khas Desa Banjarsari - Heru Totok Tri Wahono; Wisnu Mahendri (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2022)
Banjarsari Village is located in Bandarkedungmulyo District, Jombang Regency, for the plantation sector, Banjarsari Village is a typical producer of Crystal Guava because it uses fertilizers from the research of Banjarsari Village. However, the plantation products are only sold, without any other form of economic processing. Given the enormous content and benefits of crystal guava, as well as the way the Banjarsari people market their crops, the KKN STKIP PGRI Jombang students in Banjarsari Village introduced one of their programs, namely by making the basic ingredients in the manufacture of Creamy Guava snacks (Crystal Guava Chips) made of Crystal guava and of course have economic value in the economic development of the Banjarsari Village community. The purpose of this training is to maximize the use of Crystal Guava as an alternative to village businesses. The benefits that can be taken from the activity program are developing the standard of living of the people of Banjarsari Village with a creative economy as an effort that can be used as a form of improving the community's economy. This research method uses a qualitative descriptive technique. The results of this study can be seen that the people who take part in the training on making crystal guava chips have understood all the material presented in the hope that the products produced in the training can be used as souvenirs innovations typical of Banjarsari village. With this processed product, the typical crystal guava from Banjarsari Village can be known by the wider community. Keywords: Training, Typical Village, Product Inovation